Pengembangan Media Pembelajaran Kagari Berbasis Genially untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V SD Negeri Kangkung 1 - Liliyani, Salsabila; Putra, Galih Mahardika Christian (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
This study aimed to develop and evaluate the KAGARI learning media, a Genially-based tool, for fifth-grade students studying Science and Social Studies (IPAS) at SDN Kangkung 1. Based on the needs assessment, teachers and students required more engaging and effective learning materials. The Borg and Gall research and development model guided the study. A total of 39 students participated, divided into two groups for small-scale and large-scale testing. Expert validation was conducted, with the media receiving a score of 93.75% and the material receiving a score of 97.7%, both categorized as highly feasible. The results indicated a significant improvement in students' understanding of Indonesian geography after using the KAGARI media. This was supported by an N-gain score of 0.7050 and a significant t-test result (p < 0.05). These findings suggest that the KAGARI media is an effective tool for enhancing student learning outcomes in Science and Social Studies.